The Farm That Won't Wear Out - Hopkins, Cyril G. (Cyril George), 1866-1919 (Salt Lake City, UT : Project Gutenberg, 2003)
"The Farm That Won't Wear Out" by Cyril G. Hopkins is a scientific publication on agriculture written during the early 20th century. The book delves into the principles of soil fertility, emphasizing the importance of maintaining productive agricultural land through intelligent management practices. The likely overarching theme revolves around the sustainable practices necessary for agriculture to thrive without depleting essential soil nutrients. In this book, Hopkins articulates the critical need for understanding the ten essential elements of plant nutrition necessary for maintaining soil fertility. He highlights the failures of traditional farming methods, which have led to soil depletion, and advocates for methods that restore and enhance soil nutrients efficiently. Through detailed discussions and practical applications, he provides insight into the effective use of fertilizers, crop rotation, and organic matter to ensure that farming remains profitable and sustainable, ultimately aiming to reverse the trend of declining agricultural productivity in America. (This is an automatically generated summary.)
Release date is 2003-10-01
Produced by Steve Solomon. HTML version by Al Haines.
Keywords: Agriculture; Soils; Fertilizers